161k views
0 votes
2x – 1 = y + 4
3y +1 = 3х – 2​

User PeterA
by
5.4k points

1 Answer

7 votes

Answer:x=4 y=3

Explanation:

Let's solve your system by substitution.

2x−1=y+4;3y+1=3x−2

Step: Solve2x−1=y+4for y:

2x−1=y+4

2x−1+−y=y+4+−y(Add -y to both sides)

2x−y−1=4

2x−y−1+−2x=4+−2x(Add -2x to both sides)

−y−1=−2x+4

−y−1+1=−2x+4+1(Add 1 to both sides)

−y=−2x+5

−y

−1

=

−2x+5

−1

(Divide both sides by -1)

y=2x−5

Step: Substitute2x−5foryin3y+1=3x−2:

3y+1=3x−2

3(2x−5)+1=3x−2

6x−14=3x−2(Simplify both sides of the equation)

6x−14+−3x=3x−2+−3x(Add -3x to both sides)

3x−14=−2

3x−14+14=−2+14(Add 14 to both sides)

3x=12

3x

3

=

12

3

(Divide both sides by 3)

x=4

Step: Substitute4forxiny=2x−5:

y=2x−5

y=(2)(4)−5

y=3(Simplify both sides of the equation)

User Roberto Reale
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.